Allegory and metaphor in tableware - Amador, Susan, author; Getty, Nilda C. Fernández, advisor; Dormer, James T., committee member; Fahey, Patrick G., committee member; Valdez, Norberto, committee member (Colorado State University. Libraries, 1999)
Silver tableware contains the surfaces and familiar cognitive references ripe for story telling with relief, developed by chasing and repousse. The elitist connotations present in the material attract the viewer into close proximity to the work and functionality fosters an intimate relationship. The human tendency towards rituals surrounding ingesting ceremonial food and spiritually elevating drugs devise ingenious accouterments that signal entry into the ritual space, tableware being one of indicators of access. The tableware in this thesis work present allegories with diverse content, from direct, intimate function to paradox. Personal experiences, widespread in their commonality, embody a narrative significance that relates to the holloware form chosen for the particular relief images. As John Keats said "A man's life of any worth is a continual allegory-and very few eyes can see the mystery of his life ... "
Keywords: Silverwork